Development of a multi-class method to determine nitroimidazoles, nitrofurans, pharmacologically active dyes and chloramphenicol in aquaculture products by liquid chromatography-tandem mass spectrometry. (1st May 2020) - Chen, Dongmei; Delmas, Jean-Michel; Hurtaud-Pessel, Dominique; Verdon, Eric
Highlights: First method for the simultaneous detection of NFs, NIIMs, dyes and CAP. The acid hydrolysis and derivatization steps for NFs was simplified. Not only conventional NFs but other four NFs (NPIR, DNSH, PSH, AMG) were analyzed. The QuEChERS was used to extract NFs, NIIMs, dyes and CAP in aquatic products. Abstract: LC-MS/MS method was developed for the efficient identification and quantification of 21 banned substances including various nitroimidazoles, nitrofurans, pharmacologically-active dyes and chloramphenicol, respectively in aquaculture products. The sample preparation was started by acid-treatment with 2-nitrobenzaldehyde (NBA) to liberate matrix-bound residues of nitrofurans. A modified QuEChERS method was optimized for the extraction and clean-up of the target analytes. The metabolites of the four conventional nitrofurans (nitrofurantoin, furazolidone, nitrofurazone and furaltadone) and of three other nitrofurans (nifursol, nifuroxazide, and nitrovin), and an underivatizable nitrofuran (nifurpirinol) were simultaneously detected. Furthermore, 21 banned substances were quantified by LC-MS/MS with ESI using one single injection. To evaluate and validate the performance of the method, the criteria of the Decision (EC) no 2002/657 were applied. Decision limit (CCα) of target analytes ranged 0.067–1.655 μg/kg in aquaculture products. The recovery ranged 77.2%–125.6%, and the relative standard deviations of inter-day analyses (RSD) were less than 25%.